Hubungan Kerapatan Lamun dengan Kualitas Perairan di Pantai Sanur dan Terora - Asih, Ni Putu Putri Yuni; Surya Indrawan, Gede; Pratama Atmaja, Putu Satya (Journal of Marine Research and Technology, 2025)
Seagrasses are marine plants that have roots, stems, and leaves. Seagrass plays an active role in absorbing carbon dioxide (CO2), binding sediments, as a habitat for marine life, and providing a food source. Water quality affects seagrass density. This study aims to determine water quality parameters in seagrass, seagrass density, and seagrass coverage, as well as the relationship between seagrass density and water quality at Sanur Beach and Terora Beach. This research was conducted from November to December 2023. Data were collected using the purposive sampling method and transect quadrat. Data were analyzed using Principal Component Analysis (PCA) to determine the relationship between seagrass density and water quality. Based on the study's results, the parameters of temperature, pH, salinity, and dissolved oxygen (DO) are included in the optimal value for seagrass growth. There are 7 types of seagrasses found at the research location, namely Cymodocea rotundata, Cymodocea serrulata, Enhalus acoroides, Halophila ovalis, Halodule pinifolia, Syringodium isoetifolium, Thalassia hemprichii. The highest density of seagrass species in Sanur Beach is Halodule pinifolia, with an average density of 247 ind/m². The density of seagrass species in Terora Beach shows that the highest average density is found in Syringodium isoetifolium with a density of 251 ind/m². The seagrass cover in Sanur Beach is 36.56%. Meanwhile, the seagrass cover in Terora Beach is 57.81%. The results of PCA analysis at both sites showed a positive correlation between seagrass density, temperature, and pH.